Flow over a ski jumper in flight: Prediction of the aerodynamic force and flight posture with higher lift-to-drag ratio - Kim, Woojin; Lee, Hansol; Lee, Jungil; Jung, Daehan; Choi, Haecheon (Journal of Biomechanics, 2019)
Large eddy simulations (LESs)are performed to study the flow characteristics around two flight posture models of ski jumping. These models are constructed by three-dimensionally scanning two national-team ski jumpers taking flight postures. The drag and lift forces on each component of a ski jumper and skis (head with helmet and goggle, body, arms, legs and skis)and their lift-to-drag ratios are obtained. For the two posture models, the drag forces on the body, legs and skis are larger than those on the arms and head with helmet and goggle, but the lift forces on the body and skis are larger than their drag forces, resulting in high lift-to-drag ratios on the body and skis and low lift-to-drag ratio on the legs. We construct simple geometric models, such as the circular cylinder, sphere and thin rectangular plate, predicting the drag and lift forces on each component of a ski jumper and skis, and validate them with those obtained from LES. Using these geometric models, we perform a parametric study on the position angles of flight posture for higher total lift-to-drag ratio. The flight postures obtained increase the total lift-to-drag ratios by 35% and 21% from those of two base postures, respectively. Finally, LESs are performed for the postures obtained and show the increases in the total lift-to-drag ratios by 21% and 16%, respectively, indicating the adequacy of using the simple geometric models for finding a flight posture of ski jumping having a higher lift-to-drag ratio at low cost.
Keywords: Aerodynamic forces; Drag and lift forces; Flight posture; Flow charac-teristics; Lift to drag ratio; Simple geometric models; Ski jumping; Thin rectangular plate; Air; Biomechanical Phenomena; Head Protective Devices; Humans; Mechanical Phenomena; Models, Biological; Posture; Skiing; Flight posture; Large eddy simulation; Lift-to-drag ratio; Simple geometric model; Ski jumping